Queering Nollywood: Representations of Gender Non-Conformity and LGBTQ+ Identities in Ìfé (2020) - Ibe, Ibe Ogbobuike (Journal of Gender and Power, 2025)
This paper explores representations of gender non-conformity and LGBTQ+ identities in the Nigerian film Ìfé (2020), directed by Uyaiedu Ikpe-Etim. It investigates how the film challenges heteronormative norms prevalent in Nollywood through its narrative, aesthetics, and production strategies. By employing Queer Theory and Postcolonial Queer Theory, the study situates Ìfé within the broader context of Nigerian sociopolitical constraints, cinematic traditions, and the politics of queer visibility. In a country where the Same-Sex Marriage (Prohibition) Act of 2014 criminalizes queer existence and expression, the film’s emergence is both a cultural milestone and a political act of resistance. Through close textual analysis and theoretical engagement, the essay demonstrates how Ìfé redefines cinematic language by embracing queer aesthetics-intimacy, softness, and vulnerability, subverting the harsh moralistic tone often used in Nigerian cinema to depict same-sex relationships. This study also interrogates how Ìfé resists narrative closure; offering a nuanced portrayal of lesbian intimacy without punishment or moralization, thereby queering Nollywood’s storytelling structure. The film’s digital release, due to censorship from the National Film and Video Censors Board (NFVCB), signals a paradigm shift in distribution and accessibility for queer African cinema. This paper critically examines the film’s cultural reception, both locally and internationally, and its implications for future cinematic representations of LGBTQ+ identities in Nigeria. Drawing on authoritative sources, including Butler, Halberstam, Gunkel, and Ekine, it positions Ìfé as a case study in the growing body of queer African media that challenges colonial and postcolonial impositions on gender and sexuality. By highlighting how Ìfé navigates visibility, censorship, and representation, the paper underscores the transformative power of cinema as a tool for advocacy, resistance, and social change. Ultimately, this study contributes to expanding the discourse on queer African storytelling and the reimagining of Nollywood as a space for inclusive narratives.